STRATEGI KOMUNIKASI PEMASARAN MELALUI MEDIA INSTAGRAM @pekanbarushoppingmall - Resvi Dewita Sari; Oktri Permata Lani (KINEMA: Jurnal Komunikasi dan Penyiaran, 2022)
Marketing communication is a method used by companies to promote andcommunicates marketing. Instagram social media is one of the social networkingplatforms that is loved by people of all ages and is used as a medium to get various kindsof information. The focus of research on writing this thesis is how the marketingcommunication strategy used by the @pekanbarushoppingmalll. Account is throughinstagram media. The purpose of writing this thesis is to explain and analyze themarketing communication strategy used by @pekanbarushoppingmall accountis throughadvertising and sales promotion on instagram media. And to fiend out consumerresponses to the marketing communication strategy carried out by@pekanbarushoppingmall account. The type of research used is qualitative research withapproach descriptive method the data collection technique in this study used theinterviews, observations and documentation. The theory used in this research is anintegrated marketing communication or IMC. The result of the research have concludedthat strategy used by the @pekanbarushoppingmall account in terms of advertising oninstagram media include setting comunicators, setting targets, compiling messages,choosing media and channels, and evaluating communication, discount or rebates,conducting events such as give away, endorsement and reviewing product.